THE DOCUMENTATION OF SELAYAH KERINGKAM EMBROIDERY PROCESS IN SARAWAK - Genevieve, Tsar Brennam; Adyatul, Julkree; Nor Szashashiqhin, Zainal Ibidin; Qistina Donna, Lee Abdullah (UNIMAS Publisher, 2021)
This study aims to investigate the process of Selayah Keringkam embroidery in Sarawak as well as understanding the intricacy ofart and expertise in producing the SelayahKeringkam embroidery that is now becoming the status of Malay women in Sarawak. This study was conducted to examine several types and processing stages of Selayah Keringkam, thus, to understand expertise in producing Selayah Keringkam embroidery in more depth in order to maintain the uniqueness of Selayah Keringkam art for the people of Sarawak. The study involved Malay women in Sarawak who have experiences in processing and styling Selayah Keringkam. The information obtained in order to meet theobjectives of this study was taken from websites and journals that have been published and studied further through research methodology and previous studies. Research data were analyzed and displayed quantitatively and qualitatively. From the findings of this study, there are various Selayah Keringkam embroidery processes that have been researched and recorded in archives, journals and articles related to Selayah Keringkam.